Winter turning - Sutherland, Tui T. (Wings of fire, 2015)
Daring mission... or deadly mistake?Winter has been a disappointment to his royal IceWing family his whole life. When his sister, Icicle, runs away from Jade Mountain Academy, fleeing terrible crimes and possibly planning to commit more, Winter knows that they both need a second chance to make things right -- if only he can find her. Winter's new clawmates, Moon, Qibli, and Kinkajou, won't let him make this dangerous journey alone. They don't seem to understand that IceWings, the most superior of all dragon tribes, can fix their own problems. When their search leads the dragonets straight into Queen Scarlet's vicious talons, Winter is grateful to have some help. But even the bravest dragons can't follow him to the Ice Kingdom, where he'll have to face the greatest threat of all: his own family.